Report of dental care experience, preventive and restorative, in a riverside community - Amaral, Regiane Cristina do; Carvalho, Dirceu Alves; Barbosa, Jáder Lima; Sakai, Glaucy Passos (ABCS Health Sciences, 2018)
Introduction: Dental caries, despite having declined in recent years, presents groups considered polarized with highest rate of the disease, among others reasons due to the lack of access to health services. Experience report: To report an experience regarding dental care (preventive, educational and restorative) in children aged 0 to 15 years in a riverside community in the state of Pará. The first visit to the community (February 2014) lasted 3 days and was carried out as an epidemiological survey according to World Health Organization criteria. Educational and preventive activities besides dental treatments were carried out in this community. At the second visit (February 2015), again with duration of three days, oral health from this community was reevaluated. Data from the two analyzed periods, distant one year between each analysis, were compared. A total of 34 children aged 1 to 6 years according to the dmft index and 54 children/adolescents aged 7 to 15 years according to the dmft/DMFT index were examined. Statistically significant differences were found in aspects: caries (p=0.03), missing (p=0.04) and filled teeth (p=0.01). Conclusion: Access to health services associated with educational and preventive activities showed positive results in the visited riverside community.